Endothelial-to-Mesenchymal Transition, Vascular Inflammation, and Atherosclerosis - Chen, Pei-Yu; Schwartz, Martin A.; Simons, Michael (Frontiers in Cardiovascular Medicine, 2020)
Atherosclerosis is a chronic progressive disease characterized by vascular inflammation and growth of atherosclerotic plaque that eventually lead to compromise of blood flow. The disease has proven to be remarkably resistant to multiple attempts at meaningful reversal including recent strategies targeting selective inflammatory mediators. Endothelial-to-mesenchymal transition (EndMT) has recently emerged as a key driver of both vascular inflammation and plaque growth. A deeper understanding of EndMT provides new insights into the underlying biology of atherosclerosis, suggests likely molecular mechanism of atherosclerotic resistance and identifies potential new therapeutic targets.